2007
DOI: 10.1111/j.1365-2249.2007.03372.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitrotreatment of monocytes with 8-methoxypsolaren and ultraviolet A light induces dendritic cells with a tolerogenic phenotype

Abstract: SummaryExtracorporeal photopheresis (ECP) has been considered an efficient dendritic cell (DC) therapy, used for treating both T cell malignancy, as well as T cell-mediated diseases. During the ECP procedure leucocytes are exposed to photoactivable agent 8-methoxypsolaren (8-MOP) and ultraviolet (UV) A radiation (PUVA) prior to reinfusion. Despite its clinical efficacy the mechanism of action remains elusive. As it has been reported that ECP might promote the differentiation of monocytes into immature DCs, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
5
42
0
3
Order By: Relevance
“…2 B ). This is in line with the known facts that UV irradiation induces early apoptosis of tumor cells resulting in phagocytosis of dying tumor cells by APC (37). However, phagocytosis of UV-irradiated apoptotic B16 cells was less effective than phagocytosis of tumor cells after treatment with phosphatidylserine-containing liposomes (Fig.…”
Section: Resultssupporting
confidence: 90%
“…2 B ). This is in line with the known facts that UV irradiation induces early apoptosis of tumor cells resulting in phagocytosis of dying tumor cells by APC (37). However, phagocytosis of UV-irradiated apoptotic B16 cells was less effective than phagocytosis of tumor cells after treatment with phosphatidylserine-containing liposomes (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Immature human DCs have a higher susceptibility to ECP-induced apoptosis, with up to 50% of DCs undergoing apoptosis within 24 h of treatment and .90% undergoing apoptosis within 72 h of ECP treatment (55). Thereafter, the remaining viable DCs become tolerogenic with a severely diminished ability to undergo maturation in response to LPS, with a defect in inducing T cell proliferation (56). Concomitantly, there is also an increase in the levels of Tregs (57).…”
Section: Regulation Of DC Apoptosismentioning
confidence: 99%
“…Thus, it has been demonstrated that DCs, which were co-cultured with ECP-treated lymphocytes, display a reduced ability to upregulate costimulatory molecules and produce more interleukin (IL)-10 (10). In addition, it has been documented that the incubation of DCs with ECP-treated monocytes resulted in a reduced ca pacity of DCs to induce allogeneic T-cell proliferation (11). Whereas these reports are based on DCs, which are differentiated from monocytes after several days in the presence of various cytokines, studies investigating the direct influence of ECP on the immunostimulatory capacity of native human DCs are limited.…”
mentioning
confidence: 98%